Iron homeostasis in plants - a brief overview - Connorton, JM; Balk, J; Rodriguez-Celma, Jorge (Oxford University Press, 2017)
Iron plays a crucial role in biochemistry and is an essential micronutrient for plants and humans alike. Recent progress in the field has led to a better understanding of iron homeostasis in plants, and aided the production of high iron crops for improved human nutrition.